PRODUCTION OF EMPTY FRUIT BUNCH-BASED HYDROCHAR WITH HYDROTHERMAL CARBONIZATION TECHNOLOGY IN REDUCING REACTIVE BLACK 5 DYE CONTENT - Linarto, Ricky
As a country with the highest production of palm fruit in the world, the empty fruit bunch (EFB) produced in Indonesia has the potential to be made into hydrochar in adsorbing reactive black 5 dye (RB5) in textile wastewater. Thus, this research is made to identify the effects of manufacturing and adsorption operating conditions towards dye removal as well as evaluating the mechanism and performance of dye adsorption. Hydrochar is made from EFB through hydrothermal carbonization and chemically activated in varying conditions. The best hydrochar is chosen from BET, SEM, EDS, and FTIR. Langmuir and Freundlich isotherm models are used to evaluate adsorption capacity that can be obtained from the selected hydrochar. The study results showed a temperature of 195°C and a time of 3 hours 5 minutes as the optimum hydrochar making conditions. Hydrothermal treatment increases the surface area, number of pores, and the percentage of carbon atoms in the adsorbent. The best adsorption condition is achieved in pH 2, 37.5 mg/L of concentration of RB5 with 150 mg of adsorbent which can reduce 93% of the dye produced. The isotherm model follows Langmuir model with hydrochar maximum adsorption capacity being 28.18 mg/L, whereas EFB has a value of 48.68 mg/g, hence making EFB more superior compared to hydrochar. EFB adsorbent has great potential as a tertiary wastewater treatment step because it can reduce the Pt-Co value by 71%.